Reducing myeloperoxidase activity decreases inflammation and increases cellular protection in ischemic stroke - Kim, Hyeon J (J Cereb Blood Flow Metab, 2018)
Myeloperoxidase (MPO) is a pro-inflammatory enzyme abundantly secreted by activated myeloid cells after stroke. We show that when MPO activity is either blocked by the specific inhibitor 4-aminobenzoic acid hydrazide (ABAH) in wildtype (WT) mice or congenitally absent (MPO(−/−)), there was decreased cell loss, including degenerating neurons and oligodendrocytes, in the ischemic brains compared to vehicle-treated WT mice after stroke. MPO inhibition also reduced the number of activated myeloid cells after ischemia. MPO inhibition increased cytoprotective heat shock protein 70 (Hsp70) by 70% and p-Akt by 60%, while decreased the apoptotic marker p53 level by 62%, compared to vehicle-treated mice after ischemia. Similarly, MPO inhibition increased the number of Hsp70(+)/NeuN(+) cells after stroke by 60%. Notably, MPO inhibition significantly improved neurological outcome compared with the vehicle-treated group after stroke. We further found longer treatment periods resulted in larger reduction of infarct size and greater neurobehavioral improvement from MPO inhibition, even when given days after stroke. Therefore, MPO inhibition with ABAH or MPO deficiency creates a protective environment that decreased inflammatory cell recruitment and increased expression of survival factors to improve functional outcome. MPO inhibition may represent a promising therapeutic target for stroke therapy, possibly even days after stroke has occurred.